Some Ecological Aspects Of Plicofollis Argyropleuron (Siluriformes: Ariidae) In The Merbok Estuary Of Kedah - Ambri, Farahiyah Khadijah (2013)
Distribution and abundance, reproductive biology, growth pattern and their relationship to physicochemical parameters have been studied on long snouted catfish, Plicofollis argyropleuron, locally known as Goh. This study was conducted in Merbok estuary, Kedah. The fish samples were analysed from the catches of artisanal fishermen collected from Jan-10 to Jan-11. Fish are most abundant and frequently occurred in Feb-10 and their relationship with physicochemical parameters were observed. Generally, rainfall tends to be the main factor that influences their abundance and occurrence. Monthly samples from 30 to 50 of Plicofollis argyropleuron were collected with the size varied from 162 mm to 336 mm. The maturity stages of male and female were classified into five different stages namely immature, maturing, mature, ripe and spent according to physical appearances of the gonad and histological method. Their spawning season is Jan-10 and Apr-10 ( in males) and Mar-10 and Aug-10 (in females) which suggested that this species exhibit asynchronous reproductive behavior. Relative condition factor value, K for all months is more than 1 indicates the level of fish health, environmental conditions and nutrient supply are at the optimum level for this species reproduction in Merbok estuary. The growth pattern of this species is concurrent with the tropical fish growth pattern.